Internal and External Factors of Lampungese Language Maintenance in Cikoneng, Banten - Syafrizal Syafrizal; Raden Gunawan (Journal of English Language Teaching and Cultural Studies, 2018)
This study was aimed at identifying the internal factors and external factors contributing to Lampungese language maintenance in Cikoneng, Banten. When these factors are well identified, they can be used to determine certain action plans so as to effectively maintain and promote the native language. Applying a qualitative approach, the study was performed by using observation, interview, questionaires, and document study techniques. The data and information obtained were qualitatively analyzed, summarized, and compared to relevant theories and studies to draw conclusion and recommendation. It appears that the internal factors are (1) Continuity of mother tongue transfer, (2) Loyalty to mother tongue, (3) The role of Cikoneng young generation, and (4) Educational and cultural institutions. Whilst, the external factors are (1) Accommodative attitude of Sundanese and Javanese people, (2) Positive attitude of Sundanese and Javanese young generation, (3) Geographical location: Cikoneng as an open society, and (4) The role of Anyer High School. It seems that Banten Government and Sultan Ageng Tirtayasa University could play a very important role in order to assure that Cikoneng Lampungese language will be properly maintained.